PENGARUH TEMPERATUR ANIL TERHADAP KETANGGUHAN DAN KETAHANAN KOROSI KANDIDAT BAJA RINGAN PADUAN Fe-Al-Mn-Si - Ratna Kartika Sari; Sutrisna Sutrisna (ROTASI, 2013)
The world energy crisis led to the behavior of the industry aimed at improving the efficiency of the energy savings. Reduction in weight of the equipment impacts on improving efficiency and performance. For this reason, the design of vehicle aimed at the design of mass targets. Steel is the material which includes 64% of engineering materials use in the automotive industry. The addition of aluminum in steel has been shown to lower the density of alloy up to 20%. However, toughness alloys is still very low. This study examines the influence of heat treatment temperature on toughness and corrosion resistance Fe-Al-Mn-Si alloys. Heating process is carried out at a temperature of 850oc, 900oC, 950oC, 1000oC, 1050oC, for 60 minutes, followed by cooling in the muffle furnace. Tests were carried out which the test of chemical composition, microstructure test, impact test, and corrosion test using a three-electrode polarization cell method in 0.5% NaCl solution. The results showed that the Fe-Al-Mn-Si alloy has a structure of austenite to ferrite dispersed at random, where the higher the temperature structure is austenitic alloys. Highest value of impact toughness alloys Fe-Al-Mn-Si at a temperature that is equal to 3.7 J/mm2 1050oC and higher impact value with the higher annealing temperature. Highest corrosion rate on alloy of 0.05 mm / year and the lowest corrosion rate of 0.075 mm / year. This value indicates that the corrosion rate of these alloys have excellent corrosion resistance levels.